Shifts in subsurface oxygen transport and consumption patterns in a restored coastal flood plain over five years - Emilio Grande; Ruby N. Ghosh; Charles McIntire; Michael J. Freeman; Peter Regier; Nicholas D. Ward (Limnology and Oceanography, 2026)
Groundwater dissolved oxygen (DO) variability in coastal systems remains poorly understood despite its importance for biogeochemical cycling and ecosystem modeling. This study investigates temporal variability in groundwater DO and its hydro‐climatic drivers across timescales (hourly to seasonal) in a coastal floodplain at Beaver Creek, Washington, USA, a site transitioning from a freshwater forest to brackish tidal wetland following restoration of tidal influence. Using 5 years of high‐frequency (5‐min) hydro‐meteorological and continuous groundwater DO data, we applied wavelet and information theory analyses to disentangle the role of different drivers (e.g., groundwater levels, temperature, precipitation, among others) on DO dynamics. Monitoring was initiated 5 years after the site was restored but prior to subsurface conditions reaching a new steady state. We found that DO pulses related to tidal flooding events were most frequent during earlier water years, dominated by hourly, daily and multiday variability. In later years both the frequency and magnitude of these DO pulses decreased, resulting in more prolonged subsurface anoxia. These shifts in DO patterns reflect gradually changing subsurface biogeochemical conditions as the system continues to fully transition from lowland forest to brackish wetland 10 years after restoration. This study highlights the critical role of timescale‐specific analyses in understanding wetland biogeochemistry by identifying dominant drivers of DO variability and linking them to ecosystem transitions. Our scale‐aware approach offers a framework for evaluating ecosystem responses to climate change, sea‐level rise, and restoration efforts in tidal wetlands.

Corrigendum to “Phytolith spectra in respiratory aerial roots of some mangrove plants of the Indian Sunderbans and its efficacy in ancient deltaic environment reconstruction” [Quat. Int. (325), 19 March 2014, Pages 179-196] - Sayantani Das; Ruby Ghosh; Dipak Kumar Paruya; Yi-Feng Yao; Cheng-Sen Li; Subir Bera (Quaternary International, 2026)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Spatiotemporal Shift of Soil Microbes in Conservation Agriculture under a Rice-Based Cropping System at the New Alluvial Zone of Lower Gangetic Plain - Puja Singh; Susanta Dutta; Siddhartha Mukherjee; Niharendu Saha; Bishnuprasad Dash; Samrat Ghosh; Biswabara Sahu; Ruby Pate; Ahana Dey; M Jaison; Tufleuddin Biswas; Biswapati Mandal (Journal of Soil Science and Plant Nutrition, 2024)

Chloridoideae grass phytoliths can distinguish two different rainfall zones: A case study from northern parts of Western Ghats, India - Manjuree Karmakar; Ranita Biswas; Biswajit Mukherjee; Oindrila Biswas; Madhab Naskar; Dipak Kumar Paruya; Althaf Ahamed Kabeer K; Ruby Ghosh; Subir Bera (Quaternary International, 2024)

Seasonal drivers of dissolved oxygen across a tidal creek–marsh interface revealed by machine learning - Peter J. Regier; Nicholas D. Ward; Allison N. Myers‐Pigg; Jay Grate; Michael J. Freeman; Ruby N. Ghosh (Limnology and Oceanography, 2023)
Dissolved oxygen (DO) is a key biogeochemical control in coastal systems, and its concentration and drivers vary markedly through time and space. This makes it difficult to accurately represent coastal DO and associated biogeochemical processes in models, limiting our ability to predict how these systems will respond to global change. We obtained high‐frequency (5‐min) in situ measurements of DO collected at three locations across the interface of a tidal creek and coastal marsh in the Pacific Northwest, USA. Random Forest machine learning models quantified the importance of three categories of environmental drivers (Aquatic, Climatic, and Terrestrial) of DO variability across the creek–marsh interface. We selected two 4‐month datasets representing Summer and Winter seasonal periods to test two hypotheses on the dominant drivers of DO at the coastal interface. We found that the Terrestrial driver—characterized by long periods of anaerobic conditions and episodic pulses in DO after floods—was most important during the Winter, whereas the Aquatic driver—characterized by variability over tidal, diel, and lunar cycles—was most important during the Summer. We explored how future climate change scenarios could alter the drivers of DO variability using a cumulative sums driver–response framework. Our results suggest that under climate change, Aquatic and Climatic drivers may increase in importance during the Summer, potentially linked to changing metabolic regimes and sea level, with Terrestrial driver importance potentially increasing during the Winter. Our approach highlights useful methods for understanding the spatiotemporal complexity of oxygen across coastal interfaces and quantifying the relative importance of distinct environmental drivers.

Modern biotic and abiotic analogues from the surface soil of Ganga-Ghaghara-Gandak interfluves of the Central Ganga Plain (CGP), India: Implications for the palaeoecological reconstructions - Swati Tripathi; Biswajeet Thakur; Anupam Sharma; Binita Phartiyal; Sadhan Kumar Basumatary; Ruby Ghosh; Kamlesh Kumar; M.C. Manoj; Shailesh Agrawal; Anjum Farooqui; Pooja Tiwari; Korobi Saikia; et al. (CATENA, 2023)

Last 10 millennial history of Indian summer monsoon in the Bengal region – a multi-proxy reconstruction from a lacustrine archive - Ruby Ghosh; Korobi Saikia; Oindrila Biswas; Shailesh Agrawal; P. Morthekai; Mohammad Arif; Binita Phartiyal; Anupam Sharma; Neha Singh; Dipak Kumar Paruya; Pyarimohan Maharana; Mayank Shekhar; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

RNA interference and crop protection against biotic stresses - Ranjeet Kaur; Aparajita Choudhury; Sambhavana Chauhan; Arundhati Ghosh; Ruby Tiwari; Manchikatla Venkat Rajam (Physiology and Molecular Biology of Plants, 2021)

Palaeoclimate estimates based on the late Miocene to early Pleistocene wood flora of the Bengal Basin: an insight into the climatic evolution of southern Asia - Ruby Ghosh; Anwesha Biswas; Angela A. Bruch; Torsten Utescher; Illora Sen; Dipak Kumar Paruya; Anupam Guha; Sultan-Ul-Islam; Subir Bera (Palaeobiodiversity and Palaeoenvironments, 2021)

Erratum to: Floral diversity during Plio-Pleistocene Siwalik sedimentation (Kimin Formation) in Arunachal Pradesh, India, and its palaeoclimatic significance - Mahasin Ali Khan; Ruby Ghosh; Subir Bera; Robert A. Spicer; T. E. V. Spicer (Palaeobiodiversity and Palaeoenvironments, 2013)

Floral diversity during Plio-Pleistocene Siwalik sedimentation (Kimin Formation) in Arunachal Pradesh, India, and its palaeoclimatic significance - Mahasin Ali Khan; Ruby Ghosh; Subir Bera; Robert A. Spicer; T. E. V. Spicer (Palaeobiodiversity and Palaeoenvironments, 2011)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)